Impact of Brand Love on Brand Loyalty: The Moderating Role of Self-Esteem and Social Influences - Chhetri, Ashmita Dahal; Chhetri, Guna Raj (Chaturbhujeshwar Academic Journal, 2024)
This study examines the impact of brand love on brand loyalty, examining the moderating roles of self-esteem and susceptibility to normative influence (SNI) within the context of consumer behavior in Bharatpur Metropolitan City, Chitwan, Nepal. Utilizing a descriptive and causal comparative research design, the study employs a structured questionnaire survey, gathering primary data from 218 respondents through purposive sampling. The research aims to elucidate how brand love fosters brand loyalty and how self-esteem and social influences modulate this relationship. The findings reveal that respondents exhibit a moderate level of brand love, self-esteem, and susceptibility to normative influence, with brand loyalty also being moderately present. Correlation analysis indicates a significant, albeit weak, positive relationship between brand love and brand loyalty, suggesting that while emotional attachment to a brand enhances loyalty, other factors are also influential. SNI shows a weak positive correlation with brand loyalty, but this relationship is not statistically significant. Self- esteem, on the other hand, significantly negatively impacts brand loyalty. Regression results further highlight that brand love is a significant positive predictor of brand loyalty, whereas self-esteem negatively affects it. SNI does not significantly influence brand loyalty. These findings underscore the critical role of brand love in fostering loyalty and suggest that higher self esteem may reduce brand loyalty, potentially due to overconfidence or differing consumer priorities. The study contributes to understanding the dynamics of brand loyalty and the nuanced effects of psychological and social factors on consumer-brand relationships.